Gregory Clark (with Neil Cummins, Yu Hao, and Daniel Diaz Vidal). The Son Also Rises: Surnames and the History of Social Mobility. Princeton (New Jersey), Princeton University Press, 2014, XII + 364 págs., ISBN: 978-0-691-16254-6. - Minns, Chris (Investigaciones de Historia Económica, 2019)
Sin resumen